Miljøovervåking på Bouvetøya - Bakken, Vidar; Isaksen, Kjell; Mehlum, Fridtjof; Gjertz, Ian (Natur, 1997)
Keywords: Bouvetøya; biologi

Responses of terrestrial plants and invertebrates to environmental change at high latitudes - Callaghan, Terry V.; Sonesson, Mats; Sømme, Lauritz; Walton, D. W. H.; Christensen, T.; Block, W. C.; Drewry, D. J.; Laws, Richard Maitland; Pyle, John Adrian (Philosophical Transactions of the Royal Society of London. Series B: Biological Sciences, 1997)
Many invertebrates show flexibility in their life cycles and are likely to respond to changes in climate as they have in the past. However, changes in temperature and photoperiod may disturb the life cycles of some existing polar invertebrates while continuing to constrain the polewards migration of more temperate species. Higher plants are likely to have higher productivity as temperatures and atmospheric CO2 levels increase but this productivity will be reduced by exposure to increasing UV-B radiation. Higher plants migrate more slowly than the rate at which climate is predicted to change and many species will be trapped in supra-optimal climates. Both mosses and lichens can migrate faster than higher plants, propagules of non-polar species already reaching the Antarctic, but they have fewer mechanisms of responding to changing environments. Polar vegetation and ecosystems provide feedback to the climate system: positive feedbacks are associated with decreases in reflectivity and increased carbon emissions from warm ing soils. In the Antarctic, feedback and responses to environmental change will be smaller than in the Arctic because of the less responsive cryptogams which dominate the Antarctic, the paucity of Antarctic soils, and geographical barriers to plant and invertebrate migrations.
Publisher: Royal Society
Keywords: Antarktis; biologi; botanikk; klimaendringer; lav; moser; virvelløse dyr

Anatomy and microbiology of the digestive tract of the Adelie penguin - Olsen, Monica Alterskjær; Mathiesen, Svein Disch (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Antarktis; NARE 1996/97; biologi; pingviner; zoologi

Report of the Norwegian Antarctic Research Expedition 1996/97 - Winther, Jan-Gunnar (ed.) (Norsk Polarinstitutt, 1997)
Publication Title: Meddelelser
Keywords: Antarktis; NARE 1996/97; biologi; geodesi; geologi; glasiologi; oseanografi